Nuclear Bluff Learning: Nuclear Signaling in Times of Crisis - Tawfik, Dina (AUC Knowledge Fountain, 2023)
The thesis investigates the role of nuclear signaling by adopting a comparative case study approach to compare between two nuclear alert crises that occurred during the Cold War and two nuclear alert crises that occurred post-Cold War. The case studies included are as follows: the 1969 US nuclear alert; the 1973 Middle East nuclear alert; the 2017 US-North Korean nuclear alert; and the 2022 Russian nuclear alert. I investigate why leaders choose to employ this tactic despite its conspicuous dangers, and more importantly, I draw comparisons and similarities between the case studies to analyze how the Cold War nuclear alert crises can be compared to those after the Cold War ended. During this investigation, I coin a new nuclear term: “nuclear bluff learning”. This term refers to how each successive nuclear alerting leader learns from the past nuclear alerts and employs their own new tactics to further evolve the game of nuclear signaling and further their leverage in a conflict. Some nuclear ‘bluffs’ have been unsuccessful in achieving the outcomes they were intended to produce, and yet leaders continue to use this tactic by learning from mistakes of the past and transforming it to serve their interests.